Evaluation of a micro-nutrient beverage mix intervention on biochemical parameters, growth, and strength in Indian children with diverse anthropometric profiles: An in-silico study - Sahana Sringari; Surabhi Vijaykumar; Manali Sherkane; Nitika Vig; Megha Venkatesh; Suranjana Gupta; Karan Lomore; Venkatesh Kareenhalli (PLoS ONE, 2025)
Introduction Nutritional deficiencies in childhood can severely impact growth, making adequate micronutrient intake essential to prevent growth faltering. This study used an in-silico modeling framework to evaluate the impact of a micro-nutrient beverage (MNB) mix on growth, body composition, and strength in 7-to-9-year-old children within the 5th to 50th growth percentiles and diverse baseline anthropometries. Methods The model was validated against national datasets (IAP 2015 and ICMR NIN 2024) before predicting the effects of a micro-nutrient beverage (MNB) mix on a virtual population of Indian children. The population was divided into three BMI types: Type 1 (low-normal height and weight), Type 2 (low height), and Type 3 (low height and weight), each reflecting specific nutrient deficiencies. Using a crossover study design for in-silico analysis, each BMI type underwent four experimental setups to assess the effects of the MNB mix with water (MNB-W) or milk (MNB-M). Key biochemical, anthropometric, and physical strength metrics were analyzed over simulated periods of 4, 8, and 12 months. Results Both the MNB-W and MNB-M interventions significantly improved serum nutrient levels and growth parameters compared to the control group. All three BMI types exhibited notable increases in height and weight velocities, muscle mass, fat mass, and bone mineral content following the interventions. While BMI Type 3 children, who had major dietary inadequacies, showed the most pronounced improvements with the MNB-M intervention, children in BMI Types 1 and 2, with milder deficiencies, also experienced significant growth enhancements with both MNB-W and MNB-M interventions.Additionally, all BMI types showed improvements in physical strength with the MNB-M intervention, as seen in handgrip strength (HGS) and standing jump performance gains. Conclusion This in-silico study emphasized the importance of baseline nutritional status in intervention effectiveness. Results underscore the importance of multiple micronutrient intervention, especially for children with severe deficiencies, in achieving optimal growth outcomes.